2014
DOI: 10.3892/or.2014.3507
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis in MDA-MB-231 human breast carcinoma cells with an ethanol extract of Cyperus rotundus L. by activating caspases

Abstract: Abstract. Cyperus rotundus L. belongs to the Cyperaceae family and is a well documented traditional medicinal herb. Its rhizome has been reported to possess wide spectrum pharmacological activities including anti-inflammatory and antioxidant activity. However, the cellular and molecular mechanisms of the anticancer activity have not been elucidated. In the present study, we investigated the pro-apoptotic effects of C. rotundu rhizomes in a human breast carcinoma MDA-MB-231 cell model. Treatment of MDA-MB-231 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Furthermore, inhibitors of phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activatedprotein kinase (MAPK) signaling pathways failed to reverse EECR-induced apoptosis and growth inhibition. These results revealed that the pro-apoptotic activity of the EECR may be regulated by a caspase-dependent cascade through activation of both intrinsic and extrinsic signaling pathways that was not associated with ROS generation or the PI3K/Akt and MAPK pathways [107].…”
Section: Anticancer Effectmentioning
confidence: 87%
“…Furthermore, inhibitors of phosphatidylinositol 3-kinase (PI3K)/Akt and mitogen-activatedprotein kinase (MAPK) signaling pathways failed to reverse EECR-induced apoptosis and growth inhibition. These results revealed that the pro-apoptotic activity of the EECR may be regulated by a caspase-dependent cascade through activation of both intrinsic and extrinsic signaling pathways that was not associated with ROS generation or the PI3K/Akt and MAPK pathways [107].…”
Section: Anticancer Effectmentioning
confidence: 87%
“…The other species (Cyperus rotundus, Cyperus articulatus, and Cyperus esculentus) of Cyperaceae family are reported to have activities such as antioxidant, convulsion, and anthelmintic. The anticancer activity has been observed in the species of Cyperus rotundus [30,31]. It is reported that stigmasterol also has anticancer activity in a mouse model of 7,12-dimethylbenz(a)anthracene-induced skin carcinoma [32].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mitochondria mediated apoptosis is precisely regulate by Bcl-2 family proteins. Furthermore, the Bcl-2/Bax ratio is known as the ‘molecule trigger’ of apoptosis [ 35 ]. Interestingly, MET-Har-02 has insignificant influence on the ratio of Bcl-2/Bax.…”
Section: Discussionmentioning
confidence: 99%